Pengaruh Alokasi Belanja Pendidikan, Kesehatan dan Sosial Terhadap Tingkat Indeks Pembangunan Manusia Kabupaten/Kota Provinsi Aceh - Zulfadli Siregar; Erlina Erlina; Sirojuzilam Sirojuzilam (Jurnal Intervensi Sosial dan Pembangunan, 2023)
This study aims to see the effect of expenditure allocation variables in the education, health and social protection sectors on the Human Development Index (IPM) in districts/cities in Aceh province. The analytical method used in this research is multiple linear regression analysis using SPSS. The data used is the Human Development Index (IPM) and APBD expenditures for the education, health and social protection sectors for the 2021-2022 period. The results of the study show that education spending has a negative but not significant effect on the district/city HDI of Aceh Province. Social Expenditures have a positive but not significant effect on the district/city HDI of Aceh Province. The variables of Education Expenditure, Health Expenditure and Social Expenditure simultaneously influence the Human Development Index (IPM) of the districts/cities of Aceh Province. However, only 4 percent of the Aceh Province District/City Human Development Index can be explained by the three independent variables above, while the remaining 96 percent is explained by other variables not included in this study.Keywords: Education spending, Health spending, Social protection spending, Human Development Index (HDI)